Efeito da adição de MOS e FOS, associados antes ou após a extrusão, em dietas para cães - Felssner, Karla dos Santos (2013)
The goals of this study were to evaluate the effects of a Mannanoligosaccharide (MOS) and a Frutoligosaccharide (FOS) mixture in a 1:1 ratio added to a commercial diet for dogs before or after the extrusion process on the apparent digestibility coefficient of the diet sand on the metabolizable energy, nitrogen metabolism (postprandial blood urea curve, organic nitrogen balance, fecal concentration of ammonia and excretion of urinary urea) and fecal fermentation parameters (fecal pH and concentrations of short chain fatty acids). 18 adult Beagle dogs were used and randomly distributed into three treatments, being a control diet plus two diet sin which the mixture of prebiotic swere added before or after the extrusion of the ration. There was no difference in digestibility, metabolizable energy, fecal ammonia content and short-chain fatty acids (acetic, propionic and butyric) between the control diet and the ones with the addition of prebiotics. However, the dogs supplemented with prebiotics before or after extrusion, had a lower fecal pH (p<0,05) compared to those in the control diet and a reduction in the post prandial blood urea concentration (p<0,0001) was also observed in the animals receiving prebiotics, observed by the áreas below the curve of urea and it sincrement. The extrusion process did not affect the biological effects of prebiotics on the parameters evaluated in dogs. The possible mechanisms involved in the effect of prebiotics on the reduction in the concentrations of blood urea are the reduction in the formation and intestinal absorption of ammonia, favored by the reduction of intestinal pH. These findings can be considered in the use of prebiotics in clinical nutrition.